Performance Optimisation through Education and Knowledge Management Synergy: An Innovative Business Organisation Strategy - Sudi, Didih Muhamad; Jusman, Ikhsan Amar; Heriyanto (ADMAN: Journal of Contemporary Administration and Management, 2023)
In the era of globalization and intensifying business competition, business organizations are faced with the challenge of continuously improving their performance to survive and thrive. One key factor in achieving this goal is through the optimization of organizational performance. Education and knowledge management have been recognized as two crucial components that can play a strategic role in enhancing the competitiveness of an organization. This research aims to identify innovative business organization strategies to optimize their performance amidst the challenges and opportunities present in the current business environment. The research employs a qualitative approach involving the analysis of literature. It encompasses the exploration and clarification of information and content gathered from various documents and texts to establish the groundwork for analysis. The study's findings indicate that in a dynamic business environment, the synergy between education and knowledge management is key to optimizing organizational performance. Education creates a skilled workforce and a learning culture, while knowledge management ensures effective access and utilization of knowledge. The combination of continuous education, skills training, and leadership development creates an environment where employees can be responsive to market demands. Effective knowledge management facilitates collaboration and the exchange of ideas, providing the foundation for implementing innovation in a rapidly changing business landscape.